1999
DOI: 10.1210/jc.84.3.960
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of CYP21, Linked Chromosome 6p Markers, and a Sex-Specific Gene in Neonatal Screening for Congenital Adrenal Hyperplasia

Abstract: We investigated the feasibility and diagnostic utility of genotyping 9 CYP21 mutations, linked chromosome 6p markers, and a dimorphic X-Y marker from neonatal screening samples. Blood-impregnated filter papers (Guthrie cards) from 603 randomly chosen New Zealand neonates were genotyped blind to 17-hydroxyprogesterone (17-OHP) levels. Another 50 samples from Swiss and North American infants with correlative hormonal data were also genotyped. DNA was extracted, and gene-specific PCR was performed. CYP21 PCR prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
8

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 0 publications
1
46
1
8
Order By: Relevance
“…Based on plasma 17-OHP responses to ACTH stimulation, heterozygous carrier frequencies have been estimated as one in 16 for Caucasians (42). Molecular genetic screening of normal newborn infants in New Zealand showed that one in 20 were heterozygous for CYP21B mutations, which implies a disease frequency similar to that estimated in the Caucasian population (43). In our study, the detection of one homozygous and three heterozygous germline mutations in 19 patients with bilateral (21.1%), and five heterozygous germline mutations in 31 patients with unilateral incidentalomas (16.1%) suggests a higher frequency of mutations in both groups of adrenal tumors compared with that found in the general European population.…”
Section: Discussionmentioning
confidence: 91%
“…Based on plasma 17-OHP responses to ACTH stimulation, heterozygous carrier frequencies have been estimated as one in 16 for Caucasians (42). Molecular genetic screening of normal newborn infants in New Zealand showed that one in 20 were heterozygous for CYP21B mutations, which implies a disease frequency similar to that estimated in the Caucasian population (43). In our study, the detection of one homozygous and three heterozygous germline mutations in 19 patients with bilateral (21.1%), and five heterozygous germline mutations in 31 patients with unilateral incidentalomas (16.1%) suggests a higher frequency of mutations in both groups of adrenal tumors compared with that found in the general European population.…”
Section: Discussionmentioning
confidence: 91%
“…(26) recomenda que a coleta de sangue para triagem para HAC-D21OH seja feita entre 48 e 72h após o nascimento e no máximo até o final da primeira semana de vida. Os recentes trabalhos que utilizam a genotipagem de CYP21B como complemento à triagem para HAC-D21OH trouxeram dados mais objetivos entre a relação dos valores de 17OHP, as formas clínicas e o genótipo apresentado (13,(27)(28)(29)(30)(31). A maior utilização da análise molecular, entretanto, refere-se à elucidação dos casos duvidosos, evitando, assim, o tratamento desnecessário.…”
unclassified
“…Também pode ocorrer falha de amplificação de um alelo (allelic dropout) normal ou mutante durante a PCR. Para minimizar este problema, o estudo de microssatélites altamente polimórficos que flanqueiam o gene da 21-hidroxilase tem sido utilizado no diagnóstico pré-natal em adjunto ao estudo molecular do gene CYP21 (39).…”
Section: Diagnóstico Prenatalunclassified